HPLC Method for Qualitative Analysis of Acetaminophen in Pharmaceutical Painkillers (Paracetamol, Panadol, and Saridon) in Tablet Formulations (Sebha University Conference Proceedings, 2024)
This study aimed to verify the therapeutic components of the most common commercial pharmaceutical painkillers (Paracetamol, Panadol, and Saridon) and determine their degree of purity and thus protect the consumer using the high-performance liquid chromatography (HPLC) method. All ingredients were quantified in tablet formulations.  The chromatographic separation was carried out on a slim C18 column by gradient elution using a mixture of acetonitrile and water (75:25 v/v) as the solvents. The flow rate was 1.0 mL min−1 and the injection volume was 10 μL. Detection was performed at 280 nm using a photodiode array detector. The retention times (tR) of acetaminophen were observed to be 0.55 min (paracetamol), 0.53 min (panadol), and 0.53 min (saridon). The findings revealed that the retention time (tR) values for acetaminophen in all three medications were very similar. In addition, the HPLC chromatogram revealed that saridon contains two other active ingredients (saridon and propyphenazone). The tR of propyphenazone was detected to be 0.80 min (saridon). The tR of caffeine was remarked to be 1.20 min (saridon).